Crisis Communications as a Key Factor of Successful Corporate Anti-Crisis Management - T. I. Аlifanova (Управленческие науки)
The paper reviews crisis communications as the main marketing instrument of corporate anti-crisis management in its operational practice affected by the global oversupply of generic products, free access to data bases and availability of equal technical feasibility of competing agents, which lays special emphasis on intangible assets whose monetary value is proportionate to the quality of external corporate communications. Combining the mechanisms of anti-crisis management, public relations technologies, communication technologies and risk-management techniques in the modern volatile environment, crisis communication management is a generalized instrument which naturally creates the value of intangible assets, hence the company’s goodwill. The article presents the examples of successful use of crisis communications for the increase of their own capitalization by investment and financial organizations, telecommunications companies, internet providers and software developers, i. e. companies specializing in non-tangible assets and relying on the efficient use of crisis communications.